Interactions of discrete solitons with structural defects - Morandotti, R.; Eisenberg, H. S.; Mandelik, D.; Silberberg, Y.; Modotto, D.; Sorel, M.; Stanley, C. R.; Aitchison, J. S. (Opt. Lett., OL, 2003)
We investigated the interaction of discrete solitons with defect states fabricated in arrays of coupled waveguides. We achieved attractive and repulsive defects by decreasing and increasing, respectively, the spacing of one pair of waveguides in an otherwise uniform array. Linear and nonlinear propagation in the same samples show distinctly different properties. The role of the Peierls–Nabarro potential in the interaction of the soliton with the defect is discussed.
Publisher: Optica Publishing Group
Keywords: CCD cameras; instabilities; Nonlinear absorption; Phase matching; Solitons; Waveguides